1984
DOI: 10.1002/pol.1984.170220718
|View full text |Cite
|
Sign up to set email alerts
|

Cationic oligomerization of bicyclic oxalactam

Abstract: SynopsisCationic oligomerization of bicyclic oxalactam, 8-oxa-6-azabicyclo[3.2.l]octan-7-one [abbreviated as BOL (111, was carried out at 04WC with trifluoromethanesulfonic acid and borontrifluoride etherate as catalysts to obtain the oligomer mixture at high yield. From the structural analysis of the isolated dimer, a N-(2(ekarbamoyltetrahydropyran-6(e )-yl)-8-oxa-6azabicyclo[3.2.l]octan-7-one, the oligomerization proceeded through the G 6 N scission in (1) but not through the 6N-7C (amide group) scission as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1990
1990
2002
2002

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The cationic polymerization behavior of 2,6-BOL described above significantly differs from that of 8,6-BOL: The latter monomer gave a mixture of dimers and higher oligomers in the presence of cationic initiators such as trifluoromethanesulfonic acid and boron trifluoride etherate. 30 From the spectroscopic analysis of the isolated dimers from racemic and optically active 8,6-BOL, it was concluded that the cationic oligomerization involved the protonation onto the amide nitrogen of 8,6-BOL and the subsequent selective scission of the C(5)-N(6) bond, while the C(5)-0(8) bond was intact.…”
Section: Resultsmentioning
confidence: 99%
“…The cationic polymerization behavior of 2,6-BOL described above significantly differs from that of 8,6-BOL: The latter monomer gave a mixture of dimers and higher oligomers in the presence of cationic initiators such as trifluoromethanesulfonic acid and boron trifluoride etherate. 30 From the spectroscopic analysis of the isolated dimers from racemic and optically active 8,6-BOL, it was concluded that the cationic oligomerization involved the protonation onto the amide nitrogen of 8,6-BOL and the subsequent selective scission of the C(5)-N(6) bond, while the C(5)-0(8) bond was intact.…”
Section: Resultsmentioning
confidence: 99%